What youth can't do: the juvenile court and the social construction of youth offending - Chernoff, William A. (Kansas State University, 2018)
At each milestone of its development, advocates of the juvenile court have repeatedly and rightly recognized the court for what it is: a powerful instrument affecting the normal development of youth. The juvenile court is a social institution organized to achieve certain values. At its most mundane, it ensures that certain practices and beliefs actually exist somewhere in the world. At its most grandiose, it imprints these behaviors and thoughts on those involved, extending its locus of influence and transforming society itself. Because of its potential to transform people’s lives, it is important to understand the circumstances under which the juvenile court more regularly and, perhaps more zealously, reinforces what people can and cannot do. To understand social control and the juvenile court, court case records were drawn from a large, Midwestern Juvenile Court filed between January 1st, 2012 and December 31st, 2016. These records were obtained using the juvenile court’s Justice Information Leveraging System, an online, real-time court records management system available to the public. Drawing a random sample of juvenile court cases (N=582), the present study examines the effects of demeanor, context, race, social class, and gender on court imposed social control. Controlling for alternative explanations (i.e., prior involvement, offense severity, judge idiosyncrasies, and age), the present study shows that demeanor, context and race, as well as demeanor and gender affect decisions made during the juvenile court process. Among cases involving youth whose contexts were criminogenic, minority youth, more than white youth, were more likely to be detained prior to adjudication. Additionally, the effect of demeanor on disposition length among cases involving girls was greater than that observed among boys. Lastly, cases involving youth whose demeanors were disagreeable, were more likely to be detained and to receive dispositions that were longer and more severe than cases involving youth whose demeanors were agreeable. Notably, sufficient evidence was observed of effects involving offense severity and prior record on social control. Cases involving youth charged with a felony were, more than cases involving youth charged only with misdemeanors, more likely to be detained, disposed to a more severe intervention, and disposed for a longer period of time. Cases involving youth with more involved prior records generally received greater social control, particularly regarding detention and disposition length. However, mixed results were observed regarding adjudication and disposition severity. Sufficient evidence was observed to suggest that not all youth received a “first-timer discount” at adjudication. Likewise, first-timers were, compared to those with a history of court involvement (but not adjudication), more likely to receive some form of court intervention. These findings suggest new directions for juvenile court policy and practice. The juvenile court should investigate racial and gender disparity in what it does. It is possible that mundane, unintentional practices reinforce disparate social arrangements. Additionally, the court should reassess it reliance on “Just Deserts” and other graduated forms of intervention. As the latest research on adolescent development suggests (Steinberg 2007), youth are not adults, and, as such, should not be judge by adult standards.
Keywords: DisparityJuvenile court